1997
DOI: 10.1016/s0886-3350(97)80156-3
|View full text |Cite
|
Sign up to set email alerts
|

Diathermic capsulotomy versus capsulorhexis: A biomechanical study

Abstract: The mechanical quality of the diathermic capsulotomy edge is significantly less than that of the capsulorhexis edge, which indicates that the diathermic capsulotomy edge would withstand less surgical manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 10 publications
0
16
1
3
Order By: Relevance
“…Contudo, estudos histológicos demonstram diminuição de cerca de 50% na elasticidade dos bordos da capsulorrexe feita com a radiofreqüência (18)(19) . Estes fatores, teoricamente, tornariam a borda da capsulorrexe anterior mais vulnerável à ruptura (18)(19) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Contudo, estudos histológicos demonstram diminuição de cerca de 50% na elasticidade dos bordos da capsulorrexe feita com a radiofreqüência (18)(19) . Estes fatores, teoricamente, tornariam a borda da capsulorrexe anterior mais vulnerável à ruptura (18)(19) .…”
Section: Resultsunclassified
“…Estes fatores, teoricamente, tornariam a borda da capsulorrexe anterior mais vulnerável à ruptura (18)(19) . Na realidade, em nossa experiência, esta técnica permitiu realizar a capsulorrexe anterior e posterior com facilidade, segurança e previsibilidade, proporcionando assim, condições ideais para a desejável implantação da LIO dentro do saco capsular, objetivo de várias técnicas cirúrgicas (6)(7)(8)(11)(12)(13) .…”
Section: Resultsunclassified
“…[14][15][16] In contrast to PEAK-fc, HFC has been associated with a higher risk for capsule tears and intraoperative and postoperative complications than CCC. [17][18][19][20] Histological examination of HFC cuts revealed thermal damage, 21 decreasing the biomechanical stability of the anterior capsule opening. [17][18][19][20] A mechanized (vitrector-cut) anterior capsulotomy technique (vitrectorhexis) combined with IOL implantation in pediatric cataract surgery was first described in the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Krag et al 22 found that the mean extensibility (also using percentage elongation above the resting circumference at breakpoint) of their radio-frequency capsulotomy was markedly greater (P!.001) in porcine eyes (62%) than in human adult eyes (38%). The difference in mean extensibility between manual CCC and radiofrequency capsulotomies in human adult eyes (68% versus 38%, P!.001) was not observed in porcine eyes (62% versus 62%, PO.05).…”
Section: Radio-frequency Diathermy Capsulotomymentioning
confidence: 99%